Electrode System for the Determination of Microbial Populations - Matsunaga, Tadashi (1979)
Determinations of microbial populations were carried out by using a new electrode system composed of two electrodes. Each electrode was constructed from a platinum anode and a silver peroxide cathode. The anode of the reference electrode was covered with cellulose dialysis membrane. The response time of the electrode system was 15 min in culture broth, and current differences between the two electrodes were proportional to populations of microbial cells in cultures of Saccharomyces cerevisiae and Lactobacillus fermentum. Current differences were reproducible; the average relative error was 5%. Furthermore, cell populations of S. cerevisiae in a fermentor could be continuously estimated by using this electrochemical method.